2016
DOI: 10.1016/j.susc.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Fe(II)Ti(IV)O3 mixed oxide monolayer at rutile TiO2(011): Structures and reactivities

Abstract: Mixed-metal oxide monolayer grown at an oxide support is of great potential in applications like heterogeneous catalysis. In this work, the experimentally obtained ordered mixed FeTiO 3 oxide monolayer supported by rutile TiO 2 (011) surface has been carefully studied with density functional theory calculations. The genetic algorithm based optimization scheme has been employed to improve the searching capacity for possible structures, and a well ordered mixed Fe(II)Ti(IV)O 3 monolayer oxide structure much more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…We used the genetic algorithm (GA) optimization method implemented in the Universal Structure Predictor Evolutionary Xtallography code (USPEX) to search amorphous surface structures, which has been successfully applied for predicting stable structures of bulk crystal, nanoclusters, surface reconstruction, etc. , As a global optimization method, the USPEX code uses four ways, namely hereditary, mutation, transmutation, and random, to explore the configurational space for the thermodynamically stable or metastable structures. For this work, the metastable states were selected to mimic amorphous surfaces.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the genetic algorithm (GA) optimization method implemented in the Universal Structure Predictor Evolutionary Xtallography code (USPEX) to search amorphous surface structures, which has been successfully applied for predicting stable structures of bulk crystal, nanoclusters, surface reconstruction, etc. , As a global optimization method, the USPEX code uses four ways, namely hereditary, mutation, transmutation, and random, to explore the configurational space for the thermodynamically stable or metastable structures. For this work, the metastable states were selected to mimic amorphous surfaces.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Recently, computationally efficient and data-driven machine learning (ML) models are becoming alternative to theoretical catalytic research (especially in HTS), which could combine with specific chemical data sets and experts’ domain knowledge. Several groups have succeeded in employing traditional computational catalysis and ML models to reveal some intriguing findings about metal or alloy catalysts. Ma et al used a multilayer feed-forward neural network and hand-crafted features (including structural and electronic features) to make good predictions of the adsorption energy of CO on metallic alloy .…”
Section: Introductionmentioning
confidence: 99%
“…XPD patterns were simulated by multiple electron scattering simulations implemented in the EDAC package . The atom clusters were constructed from the atom coordinates determined in DFT simulations for various surface models . The size and the scattering volume of the cluster are defined by R max which is constrained by the computation time.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…This phase segregation indicates that the two surface compositions formed what is known as line phases in bulk phase diagrams, suggesting that these two compositions form particularly stable, low energy surface phases. The details of our previous experimental studies can be found in ref and for the DFT simulations in ref .…”
Section: Introductionmentioning
confidence: 99%
“…The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 20 For each 2×1 surface cell of rutile TiO 2 (011), four TiO 2 units are exposed, and they have the same height on an unreconstructed surface while two of them rise above the other two on a 2×1 reconstructed surface. In a very recent work, we have reported an ordered Fe/Ti mixed oxide surface layer on the rutile TiO 2 (011) surface through combined experimental and computational studies 22 . We performed calculations in a similar way in the current work to search for the mixed oxide surface containing 1/3 M...…”
Section: Calculated Structures Of Mixed Oxide Monolayer Surfacementioning
confidence: 99%